Diet-Derived Halogenated Metabolite from the Sea Hare Aplysia parvula - Vairappan, Charles S.; P. Anangdan, Sangeetha; Matsunaga, Shigeki (Malaysian Journal of Science, 2009)
As part of our continuous interest in the diversity of halogenated metabolites in the red algae genus Laurencia and their grazers, the sea hare genus Aplysia in Sabah coastal waters, we report the chemical composition of Aplysia parvula collected from Sepanggar Island, Kota Kinabalu. Chemical analysis resulted in the isolation and identification of three sesquiterpenes; palisadin A (1), iso-obtusol (2) and elatol (3). Compounds were present as 13.9%, 6.7%, and 8.5% of crude extract, respectively. A similar analysis of its diet from the same location, Laurencia snackeyi (Weber-van Bosse) Masuda and Laurencia majuscula (Harvey) Lucas, showed the existence of palisadin A, palisadin B, aplysistatin and 5-acetoxypalisadin B in Laurencia snackeyi, while Laurencia majuscula contained elatol and isoobtusol. Hence, it is suggestive that A. parvula is capable of selective sequestering of compounds derived from its diet. Based on the chemicals sequestered, it is confirmed that A. parvula is an oligophagous feeder. Its ability to selectively sequester palisadin A and not the other syndreans, reflects on the complexity of its digestive glands. All three compounds also showed potent antimicrobial, antifeedant and cytotoxic activities. Sehubungan dengan minat kami dalam penyelidikan sebatian berhalogen ‘seahare’ dari perairan Sabah, kami ingin melaporkan komposisi kimia sebatian berhalogen dari Aplysia parvula dari Pulau Sepanggar, Kota Kinabalu. Hasil kajian telah membawa kepada pemencilan dan identifikasi tiga sesquiterpene; Palisadin A (1), iso-obtusol (2) and elatol (3). Sebatian-sebatian ini wujud dalam kuantiti yang signifikan 13.9%, 6.7%, and 8.5% dalam esktrak kasarnya ‘sea hare’ yang dikaji. Analisis kimia sedemikian keatas dietnya, Laurencia snackeyi (Weber-van Bosse) Masuda and Laurencia majuscula (Harvey) Lucas, telah menunjukkan kehadiran palisadin A, palisadin B, aplysistatin and 5-acetoxypalisadin B dalam Laurencia snackeyi, manakala Laurencia majuscula mengandungi elatol and isoobtusol. Maka, dapat disyorkan bahawa A. parvula dapat melakukan menepuan sebatian kimia daripada dietnya secara selektif. Berdasarkan bahan kimia yang ditepukan, dapat dikenalpasti bahawa A. parvula merupakan pemakan oligofagus. Kebolehannya untuk melakukan penemuan selektif terhadap palisadin A dan bukan ‘syndrean’ yang lain dapat membayangkan betapa kompleksnya kelenjar penghadamannya. Semua ketiga-tiga sebatian ini telah menunjukkan aktiviti antimikrob, ‘antifeedant’ dan sititoksik.